Leadership Training For Students To Improve The Ability And Extension Of Animal Husbandry And Health In The Community Of Katol Timur Village - Bahruddin, Ahmad; Takwallo, Takwallo; Hoirul , Hoirul; Lutfi, Mohammad Lutfianto (CV. Pustaka An Nur, 2025)
Katol Timur is one of the villages located in Kokop District, Bangkalan Regency, East Java Province, Indonesia. East Katol Village has the potential to be improved both in terms of human resources and natural resources, from the human resources sector, many of the people of East Katol have received education up to high school and even to the lecture level, while from the natural resources sector, some of the people of East Katol have become farmers, ranchers, and entrepreneurs, but for now education really needs attention because many students are decreasing in terms of their enthusiasm for learning and self-development, while in the aspect of animal husbandry, there is also a problem that is quite worrying because many of the livestock are attacked by disease, especially cows. The purpose of this service is to provide awareness to students and education to the community in preventing the spread of viruses in livestock. This research uses the Participatory Action Research (PAR) method for one full month by engaging directly with the local community. The results of this activity are that students have an increased awareness of the importance of education and skills and the community can find out how to prevent the spread of viruses to livestock, so that they do not have large losses.